DISPORAPAR STRATEGY IN SUBMITTING INFORMATION BASED ON CURRENT TECHNOLOGY - Wulandary, Roro Merry Chornelia (Universitas Islam Malang, 2025)
DISPORAPAR (Department of Youth, Sports, and Tourism) is a regional system that includes elements of implementing government affairs which are the authority of the region, and is led by a Head of Service who has the task of accompanying or assisting the Regent in carrying out government affairs in the tourism section in accordance with the authorities and provisions of the law. Talking about people's satisfaction with the services provided in the Malang box, many reports complained that the service time was slow. However, as time goes by, the responsiveness of the City of Malang has increased significantly, this is evidenced by the decrease in the number of complaints reported every month in 2020chain efficiency, and enhance bilateral trade cooperation.